(untitled) (London, 1990)
Compares, contrasts and evaluates the nature, scale and direction of industry-academic interactions in Japan and Europe, with particular reference to the UK.
Keywords: Nghiên cứu công nghiệp,Research, Industrial; Nhật Bản,Japan